Group selection: The quest for social preferences - Marcus Salomonsson (Stockholm School of Economics, The Economic Research Institute (EFI), 2009)
This paper surveys the literature on group selection. I describe the early contributions and the group selection controversy. I also describe the main approaches to group selection in the recent literature; fixation, assortative group formation, and reproductive externalities.
Keywords: C70; D03; D62; D64; 330; Altruism; spite; externalities; conformity; fixation; signalling